Novel impedance measurement technique for soluble solid content determination of banana - Ibrahim, Nur Ul Atikah; Abd Aziz, Samsuzana; Mat Nawi, Nazmi (Universiti Putra Malaysia Press, 2017)
Soluble solid content (SSC) is one of the important traits that indicate the ripeness of banana fruits. Determination of SSC for banana often requires destructive laboratory analysis on the fruit. An impedance measurement technique was investigated as a non-destructive approach for SSC determination of bananas. A pair of electrocardiogram (ECG) electrode connected to an impedance analyser board was used to measure the impedance value of bananas over the frequency of 19.5 to 20.5 KHz. The SSC measurement was conducted using a pocket refractometer and data was analysed to correlate SSC with impedance values. It was found that the mean of impedance, Z decreased from 10.01 to 99.93 KO at the frequency of 20 KHz, while the mean value of SSC increased from 0.58 to 4.93 % Brix from day 1 to day 8. The best correlation between impedance and SSC was found at 20 KHz, with the coefficient of determination, R2 of 0.87. This result indicates the potential of impedance measurement in predicting SSC of banana fruits.